2016
DOI: 10.1007/s10640-015-9990-1
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Climate Policy and Foreign Direct Investment with Firm and Country Heterogeneity

Abstract: We contribute to the debate on the impact of unilateral climate policy with a two-country two-…rm international oligopoly model accounting for endogenous plant location and heterogeneity in both country size and …rm's emissions technology. Our results suggest that, if the carbon price di¤erential is moderate as compared to unit transport costs and the relative size of the highly regulated country is big enough, a no relocation equilibrium may prevail also in the long run. A large market asymmetry coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…, 2015; Sanna-Randaccio et al. , 2017), licensing (Kamien et al. , 1992; Banerjee and Poddar, 2019), or internal transfer through multinational (Ethier and Markusen, 1996; Fosfuri et al.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…, 2015; Sanna-Randaccio et al. , 2017), licensing (Kamien et al. , 1992; Banerjee and Poddar, 2019), or internal transfer through multinational (Ethier and Markusen, 1996; Fosfuri et al.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…Petrakis and Xepapadeas, 2003;Ulph and Valentini, 2001;Abe and Zhao, 2005;Ikefuji et al, 2016). Finally, a part of them developed the analysis under the assumption of country asymmetry (Zeng and Zhao, 2009;Sanna-Randaccio and Sestini, 2012), or both country and firm heterogeneity (Sanna-Randaccio et al, 2016) with exogenous unilateral climate policies. In our case, we do not focus on the effects of unilateral policies on firms' location.…”
Section: Related Literaturementioning
confidence: 99%
“…Finally, we contribute to the debate on the incentive to relocate manufacturing activities to react to unilateral climate policy, thereby avoiding tax compliance. In a large strand of theoretical research, several arguments are found both in favor and against the possible shift of domestic activities abroad due to unilateral carbon taxes, whereas the empirical literature provides mixed evidence (e.g., Ikefuji et al., 2016; Sanna‐Randaccio et al., 2017). Although we do not introduce an international oligopoly, we observe that there is no incentive for firms to relocate in presence of the N‐RQ tax when it is targeted to consumers.…”
Section: Introductionmentioning
confidence: 99%